Response to comments on our article (Yin YL et al., Parasit Vectors, 10.1186/s13071-021-04739-w) by Yuqing Wang and colleagues - Yan-Ling Yin; Xin Yang; Guang-Hui Zhao (Parasites & Vectors, 2021)
Abstract This letter responds to comments on our article (Yin YL et al., Parasit Vectors, 10.1186/s13071-021-04739-w) by Yuqing Wang and colleagues, who wrote a letter entitled “Microarray analysis of circular RNAs in HCT-8 cells infected with Cryptosporidium parvum ” and discussed statistical procedures for microarray analysis during C. parvum infection. To further confirm our data, in this letter, a common R package for analyses of differentially expressed genes, namely DESeq2, with Benjamini-Hochberg correction, was used to analyze our microarray data and identified 26 significantly differentially expressed circRNAs using adjusted P value < 0.05 and | Log 2 (fold change [FC]) | ≥ 1.0, including our circRNA ciRS-7 of interest. Therefore, the protocol for selecting circRNAs of interest for further study in our article is acceptable and did not affect the subsequent scientific findings in our article.